Exemption from medical confidentiality rule in criminal cases under Article 180 § 2 of the Polish Code of Criminal Procedure - reflections in the context of caring for the patient’s welfare and the ethos of the doctor’s profession - Mazur-Lesińska, Diana; Kasprzak, Anna; Kułaga, Monika; Grzybek, Monika; Szostak, Barbara; Wielgosz-Biała, Sylwia; Tyszkiewicz, Krzysztof; Łozowski, Borys; Kasprzak, Małgorzata; Wilczyńska, Barbara (Journal of Education, Health and Sport, 2025)
The regulations of the amended Polish Code of Medical Ethics, which entered into force at the beginning of 2025, upheld the doctor’s obligation to maintain medical confidentiality. This obligation is so entrenched not only in law but also in social awareness, that it is unimaginable to omit it in any act regulating the principles of medical ethics. Both at the international and national level, the duty to maintain medical confidentiality is strongly established culturally, historically and normatively. The purpose of this article is to draw attention to the art. 180 § 2 of the Polish Code of Criminal Procedure, as a regulation stipulating that the rule of medical confidentiality is not absolute. The following goal is to analyze the circumstances and grounds for exemption from this rule in accordance with the provisions of the discussed article. This will allow us to achieve the general purpose of the present statement, i.e. to make doctors aware of the circumstances that may result in releasing the from the obligation to maintain medical confidentiality.